2010
DOI: 10.1002/jnr.22550
|View full text |Cite
|
Sign up to set email alerts
|

Maternal stress affects postnatal growth and the pituitary expression of prolactin in mouse offspring

Abstract: Maternal stress exerts long-lasting psychiatric and somatic on offspring, which persist into adulthood. However, the effect of maternal stress on the postnatal growth of pups has not been widely reported. In this study, we found that maternal immobilization stress (IS) during lactation resulted in low body weight of male mouse offspring, which persisted after weaning. Despite free access to chow, IS induced maternal malnutrition and decreased the serum insulin-like growth factor-1 (IGF-1) levels in the mothers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 58 publications
2
8
0
Order By: Relevance
“…Similar results were also obtained by Hauser and colleagues [52]. Gao and colleagues [56] proposed that the effects of prenatal stress on offspring’s body weight may relate to maternal malnutrition and to significant reductions in serum levels of insulin-like growth factor-1, growth hormone and prolactin. Additionally, the long-term reductions in body weight may also be indirectly mediated via PNC-dependent modulation of HPA reactivity.…”
Section: Discussionsupporting
confidence: 79%
“…Similar results were also obtained by Hauser and colleagues [52]. Gao and colleagues [56] proposed that the effects of prenatal stress on offspring’s body weight may relate to maternal malnutrition and to significant reductions in serum levels of insulin-like growth factor-1, growth hormone and prolactin. Additionally, the long-term reductions in body weight may also be indirectly mediated via PNC-dependent modulation of HPA reactivity.…”
Section: Discussionsupporting
confidence: 79%
“…Ether exposure and immobilisation stimulate PRL secretion in male rats . A CRF antagonist, α‐helical CRF , has been shown to suppress immobilisation‐induced PRL release in the rat , and the CRF 1 antagonist CP‐154,526 has been shown to inhibit hypoxia‐induced PRL expression in the rat pituitary . Taken together with the results of the present study, this suggests that CRF stimulates PRL secretion through CRF 1 in lactotrophs during stress.…”
Section: Discussionsupporting
confidence: 79%
“…The present study provides evidence that the distribution patterns of CRF 1 ‐LI are widely distributed in the pituitary and that this is influenced by adrenalectomy. These findings contribute to a better understanding of the roles of CRF in pituitary functions because many studies have suggested that stress and CRF can alter the pituitary functions involved in development, reproduction and lactation . We found that CRF 1 ‐LI was widely distributed in the anterior, intermediate and posterior lobes of the pituitary by using an antiserum against the 177–188 amino acid residue fragment of the first extracellular loop of rat CRF 1 .…”
Section: Discussionmentioning
confidence: 51%
“…Moreover, stress leads to an increase in anxiety-like behavior (Conrad et al, 1999; Vyas and Chattarji, 2004), while a previous report (Christakis et al, 2012) has found that young mice receiving excessive periods of sensory stimulation show a decrease in anxiety-like behavior. Stress can also affect body weight gain (Vyas et al, 2002; Gao et al, 2011); however, we found no difference in body weights between controls and mice exposed to sensory stimulation (Fig. 3 a ).…”
Section: Discussionmentioning
confidence: 62%